Effectiveness of Problem Based Learning Model on Creative Thinking in Senior High School - Mita Intan Sari; Moch. Rio Pambudi; Benter Oseno Gudu; Duratul Ain Tholibon (JAMBURA GEO EDUCATION JOURNAL, 2023)
In Indonesia, research show inadequacy in creative thinking skills among students with only about 2% being proficient in tackling problems of moderate to high difficulty according to TIMSS research. At SMA Negeri 1 Papar, the challenge of low creative thinking skills of students is evident in test results. with an average daily test score of 70 reflecting this concern. Nonetheless, the latent potential to develop creative thinking skills exists within Indonesian students, thus the need to encourage teachers to use appropriate educational strategies. To that end, the Problem-Based Learning (PBL) model emerged as an appropriate solution to address the shortcomings in students' creative thinking skills. However, little knowledge is available in this important area. This research focuses on assessing the impact of the PBL model on students' creative thinking skills by using a quasi-experimental methodology. The experiment involved students in class XI-IIS 1 (36 students) as the experimental class and XI-IIS 3 (34 students) as the control class in the even semester of the 2022/2023 academic year at SMA Negeri 1 Papar. Using essay questions as an assessment tool, the data were analyzed using SPSS 23 for Windows through a t-test, with a significance level of 0.05. In particular, a considerable difference was observed between the experimental group using the PBL model and the control group using the conventional approach. The results of the hypothesis test showed a significance level of 0.000, underscoring the potential of the PBL model in fostering higher creative thinking ability among students, as evidenced by its striking difference with a significancethresholdof 0.05. The findings are useful to Educators, teachers, parents and students. The study recommended that PBL can be adopted and used to teach in all subject areas in the currica inorder to help develop the creative thinking skills of students.